Optimalisasi Program BPJS Tenaga Kerja Dalam Upaya Meningkatkan Produktifitas Kerja : Study di PT. MAINCOMINDO PRATAMA - Anudiyan Amir Mas’ud; Dita Rachmawati; Jassica Aulia Virginia (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
The purpose of this research is to know the environmental condition of work and performance of employees at BPJS Ketenagakerjaan. In this research, the author made comparisons between environmental conditions and the performance of employees at BPJS Ketenagakerjaan Maincomindopratama. BPJS Ketenagakerjaan Kota Jambi, as a government institution, is responsible for the provision of services to the community in its working area. The provision of services to BPJS Ketenagakerjaan Maincomindopratama is based on awareness of the task, responsibility, and high taste to carry out a good service so that people are satisfied. BPJS Ketenagakerjaan Kota Jambi is a social security program responsible for the state providing social and economic protection to the community. The constant value of 0,909 means that if the working environment variable (X) is 0,909, then the performance variable (Y) is worth 0,909. Furthermore, with the simple linear regression equation above, there is a variable regression coefficient for work environment, which is a positive value of 0.608. If the value of the working environment coefficient is positive, changes to the work environment variables will result in a directional change in the performance variable. In this study, the contribution of the working environment to the performance of 0.608 can be analyzed. This means that if the working environment at BPJS Ketenagakerjaan Kota Jambi increased by 1%, employee ’performance would increase by 297.7%. Working environment on BPJS high employment with an average score of 170,75. Furthermore, employee performance at BPJS Manpower is very high, with an average score of 176. According to the hypothesis test, there is a significant relationship between the working environment and employee performance in BPJS employment. This is evidenced by the comparison between the calculated T value and the t table (4,056> 0,3081). The working environment can affect performance by 29.7%, and the remaining 73.3% is influenced by other variables not examined in this study.